Fiscal Management of Scaled-Up Aid - Fletcher, Kevin (International Monetary Fund, 2008)
The international community has committed to scaling up aid and improving aid delivery to low-income countries to help them meet the Millennium Development Goals. Other "emerging" donors, public and private, are increasing their assistance, and debt-relief initiatives are creating space for new borrowing. Remittances to low-income countries have been on a precipitous rise, and many countries are benefiting from high commodity prices. Fiscal Management of Scaled-Up Aid explores approaches to the sound fiscal management that will be required to ensure effective and sustainable use of these flows. With a medium-term perspective and efficient use of resources in mind, this paper addresses questions that shape fiscal policy response to scaled-up aid. Drawing on IMF Fiscal Affairs Department technical assistance to member countries, it outlines factors that should be taken into account in preparing an action plan for public financial management reform and proposes specific measures that will assist countries in strengthening fiscal institutions.